(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to analyze the Time Dependent System Availability (TDSA) and identify the most sensitive component/unit of Poly Ethylene Terephthalate (PET) Bottle Hot Drink Filling System of a beverage Industry with Markovian approach. TDSA and Mean time between failures (MTBF) is computed for system concerned. The industrial system chosen includes five components namely Blow Moulding Machine, Filling Machine, Cooling Machine, Labeling Machine and Coding Machine. Transition diagram of the system has been developed and respective Chapman-Kolmogorov equations are originated. The derived equations are further simplified by an advance and receptive method acknowledged as adjustive step size control Runge-Kutta method. On basis of TDSA analysis most sensitive unit/component has been identified and maintenance priorities to other units/components have been assigned.